SYNTHESIS, CHARACTERISATION AND ANTIMICROBIAL STUDIES OF MIXED LIGANDS METAL (II) COMPLEXES OF SULFAMETHOXAZOLE AND N,N- DONORS HETEROCYCLES - Eugene-Osoikhia (Nee Adebesin), Tunmise T; Aleem, A.O; Ayeni, F (FUDMA Journal of Sciences, 2020)
Two mixed ligands of sulfamethoxazole (SMX) with N,N donor heterocycles: 1,10-phenanthroline (phen) and 2,2′-bipyridine (bipy) metal complexes having the composition [M(SMX)(phen)X].nH2O and [M(SMX)(bipy)X].nH2O (where M = Zn(II) , Co(II) , Fe (II), Mn (II),Cu(II) ; X = SO4/Cl2) have been synthesised and characterised by physicochemical methods based on their solubility , metal analysis, infrared and UV-Visible techniques. Infrared spectra data showed SMX as a bidentate ligand coordinating to the metals through the N atom of the sulfonamide group ((3195-3030cm-1) and oxygen atom of the sulfonyl moiety (1158-1103 cm-1) while the heterocycles also bonded as bidentate ligands through their diimine nitrogen atoms (1606-1423 cm-1). The electronic spectra data indicated that all the metal(II) complexes were monomeric and octahedral. The in-vitro antimicrobial studies of these complexes and their ligands against environmental strains of microorganisms: Bacillus subtilis, Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, Aspergillus niger and Candida albicans showed that SMX-phen metal complexes [M(SMX)(phen)X].nH2O are better heterocycle with zone of inhibition in the range 28-10mm to combine with SMX for the enhancement of its antimicrobial spectrum this may be due to their more extensive aromatic ring system which gave better lipophilicity, hence aided cell membrane penetration and promoted hostile intracellular interactions leading to death of microoganisms.